Health effects of transport noise - Welch D; Shepherd D; Dirks KN; Reddy R (Taylor and Francis Group, 2023)
The relationship between transport noise and health outcomes is complex, in part because of the large number of factors involved as well as the range of health impacts, both direct and indirect. To enable the reader to come to grips with the complexity, we have divided the health outcomes into groups: those that are more directly linked to transport noise exposure and those that are more indirectly linked. Four health outcomes, namely annoyance, cognitive disruption, sleep problems, and noise-induced hearing loss, can be directly attributable to transport noise exposure. Less direct outcomes are stress, mental health, metabolic health, cardiovascular health, and overall health-related quality of life. Stress may occur as a direct response to noise, or may occur in response to the aforementioned direct effects. The stress response is a survival mechanism in the short term, but in the long term, stress may lead to systemic health conditions, namely metabolic and cardiovascular outcomes, and to mental health conditions. Finally, a global health outcome that incorporates all of the more direct outcomes is health-related quality of life. Other exposures associated with transport noise that may explain parts of the health outcomes need to be acknowledged, including exposure to social inequities, air pollution, and vibration. These may all be more likely to be experienced by people who are exposed to transport noise in the community and may thus influence the outcomes. Finally, transport noise appears to have more impact on health in those who are noise sensitive, thus noise sensitivity is a key moderator of all the effects observed.
Keywords: Noise; noise-induced hearingloss; cognition; sleep; annoyance; stress; mentalhealth; metabolic; cardiovascular; burden ofdisease; health-relatedquality of life